The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/admsci10010015
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the Relationship between Personal Values and Sustainability—A TMO Case Study

Abstract: Sustainability is associated with many contemporary challenges facing society, prompting sustainability initiatives and research in this field. An emerging strand of research has sought to investigate sustainability as a function of values. Given that values determine and predict perceptions, attitudes and behaviors, understanding employees’ underlying values would provide important insights on how values relate to sustainability-related actions. However, there is a gap in knowledge around individual actors’ r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 114 publications
(150 reference statements)
0
14
0
Order By: Relevance
“…The theoretical implications of this study may be directed to holistic considerations of the associations between the investigated variables, where the influence of leaders' CVs and IVs on their democratic behavior should be considered simultaneously. We connected together dispersed cognitions concerning (1) the impact of personal values on leadership style [3,11,31,32], (2) the impact of personal values on achieving sustainable working and behavior [41,46,47,109], and (3) cognitions about how leadership contributes to the achievement of sustainable goals via the creation of socially responsible organizations [40,[43][44][45]. We concluded that democratic leadership contributes to the sustainable working and behavior of organizations.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
See 2 more Smart Citations
“…The theoretical implications of this study may be directed to holistic considerations of the associations between the investigated variables, where the influence of leaders' CVs and IVs on their democratic behavior should be considered simultaneously. We connected together dispersed cognitions concerning (1) the impact of personal values on leadership style [3,11,31,32], (2) the impact of personal values on achieving sustainable working and behavior [41,46,47,109], and (3) cognitions about how leadership contributes to the achievement of sustainable goals via the creation of socially responsible organizations [40,[43][44][45]. We concluded that democratic leadership contributes to the sustainable working and behavior of organizations.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
“…From the current perspective, one of the most challenging tasks for leaders in circumstances of constantly evolving organizations is concern for sustainable development [40][41][42]. Thus, there have been several studies examining the role of leadership in the creation of the sustainable working behavior of organizations [40] by emphasizing the role of ethical leadership [43,44], servant leadership [43], and transformational leadership [45] in corporate social responsibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It thus becomes increasingly important for businesses to treat their employees with respect and appreciation, and the efficiency of a business, enterprise, or industry depends on the satisfaction of the EV (Joseph, 2019). Most scientists mean by the EV a certain system of beliefs that prioritize a person and predetermine a conscious manifestation in relationships at work or in society (Rickaby, Glass & Fernie, 2020). It is personal values, as an integral part of a person, that determines where he invests his energy, resources, and time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is personal values, as an integral part of a person, that determines where he invests his energy, resources, and time. The results of modern research indicate a direct relationship between the EV (Rickaby, Glass & Fernie, 2020;Mazilescu et al, 2021;Bolis et al, 2021) and management (Rickaby, Glass & Fernie, 2020;Nedelko & Potocan, 2021;Mazilescu et al, 2021) on organizational performance by influencing labor productivity. Thus, the EV is a decisive factor in labor productivity, and effective Personnel Management is the basis of the key to its increase.…”
Section: Literature Reviewmentioning
confidence: 99%